Pengaturan Corporate Social Responsibility Berdasarkan Guiding Principles on Business and Human Rights - Gusti Fadhil Fithrian Luthfan (Lex Renaissance, 2019)
This study aims to analyze the role of UNGP in constructing CSR legal policies in Indonesia and the implementation of CSR for companies, in order to create effective, targeted and beneficial CSR for the country, companies and society. This research is a normative study using a statutory approach, historical approach, conceptual approach and comparative approach. The results showed that according to UNGP, there is a principle of the company's obligation to respect human rights, so the company has a tool for accountability with human rights due diligence. This human rights due diligence serves to identify, prevent, mitigate and account for the impact of human rights violations that arise. In Indonesia, these UNGP principles need to be adopted in legislation such as that of France in order to create an effective, targeted and useful CSR.